2017
DOI: 10.2174/1874350101710010127
|View full text |Cite
|
Sign up to set email alerts
|

At-Risk Teachers: The Association Between Burnout Levels and Emotional Appraisal Processes

Abstract: Background:Teachers are at-risk of burnout due to continuous emotional demands. Existing research suggests that there is a strong relationship between the burnout phenomenon and teachers' propensity to experience unpleasant emotions. Objective:The current study examined whether teachers' levels of burnout affect the process by which they appraise school-life events that elicit negative emotions. Methods:Participants were 316 school teachers. Teachers' appraisal of both students' negative emotion intensity (SAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…The current study goes further by showing that reported praxis shock impacts on burnout. It should be noted that the findings by Fiorilli et al (2017) indicate that teachers who may be undergoing the experience of praxis shock may interpret students' actions in a more negative way -this may be associated with student-related burnout.…”
Section: Resultsmentioning
confidence: 98%
“…The current study goes further by showing that reported praxis shock impacts on burnout. It should be noted that the findings by Fiorilli et al (2017) indicate that teachers who may be undergoing the experience of praxis shock may interpret students' actions in a more negative way -this may be associated with student-related burnout.…”
Section: Resultsmentioning
confidence: 98%
“…Emotions and emotional regulation are at the core of the teaching profession [8,41,[55][56][57]. Consistently, when teachers perceive themselves as able to properly manage their emotions, they perform and feel better about their job [8,58,59].…”
Section: Teachers' Emotions and Hedonic Balancementioning
confidence: 99%
“…[1]. Current psychological literature widely addresses the role of teachers' personal resources [2][3][4][5][6][7], relationships with students [8,9], and individual professional resources [10,11] in managing the mentioned challenges. Despite the meaningful role of the teacher's individual contributions to these issues, collaborative practices and strategies seem to better fit such needs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, several studies addressed the associations between teachers' burnout levels and such dimensions including job satisfaction, selfand collective efficacy, positive attitudes toward their profession. Job satisfaction, namely how content an individual is about his/her job experience, plays a crucial role in promoting well-being [8,9]. Similarly, self-efficacy at work may positively influence teachers' job experience [31 -35].…”
Section: Protective Factors In Teachers' Burnoutmentioning
confidence: 99%